Sustentabilidad E Historia Oral: Huellas En El Tiempo. Conceptos Generadores De Nuevo Conocimiento Para La AcciÃ³n Ciudadana En El Siglo XXI - Spadaro, Gabriela Scartascini; Melchor, Vilma Zoraida RodrÃguez; Curiel, MarÃa Guadalupe Talavera (European Scientific Journal, ESJ, 2017)
For several decades, sustainability has been positioned as a paradigmatic concept in relation to the present and the future of our planet. It is a transverse discursive axis in front of countless issues that lead our daily life while trying to preserve, protect or recover it. In recent years, it has surpassed the field of ecology since it has been adopted by different fields that have established specific meanings. Its constant application has been reflected in areas as diverse as environment, tourism, economy, international politics, corporate affairs, education, and even gastronomy. As for Oral History, since Allan Nevins to date, its credibility and validity were strengthened and valued. In many parts of the world, the twentieth century regained its national, regional and local history through the testimonies of witnesses and protagonists of events that someone, perhaps, had wanted to keep in oblivion. Currently, new issues and problems arise to be considered from the perspective of Oral History, as a valuable resource for the recovery of perspectives, angles, and scope of information, in those same areas that are covered by the need to incorporate into the sustainability in its discourse. The objective of this proposal is to expose the historical evolution of both the sustainability notion and Oral History as concepts that have passed through the twentieth century and have been constituted as generators of new knowledge articulated with the action of citizens committed to their cultural and natural heritage, history and identity.